Effects of Microecological Preparations on Obese Patients after Bariatric Surgery: A Systematic Review and Meta-Analysis. (31st May 2020) - Zhu, Hanfei; Ren, Ziqi; Zang, Yan; Hua, Hongxia; Lu, Jinling; Xu, Qin; Zhu, Shuqin
Abstract : Vitamin deficiency, bacterial overgrowth, and gastrointestinal symptoms can be detected in obese patients after bariatric surgery that influences their quality of life (QoL) and weight. It is unclear if microecological preparations benefit obese patients following bariatric surgery. The aim of this study is to investigate the effects of microecological preparations on QoL, excess weight loss (EWL), and levels of vitamin B12 and inflammatory markers. We searched seven databases to identify reports published till December 1, 2019, and included randomized controlled trials investigating the effects of microecological preparations in obese adults undergoing bariatric surgery. The primary outcomes included QoL and EWL, while secondary outcomes comprised serum levels of vitamin B12, interleukin 6, TNF- α, and C-reactive protein (CRP). Study bias was analyzed using the Cochrane risk-of-bias tool. Statistical analyses were performed using Review Manager. The mean difference in outcomes was calculated using standardized mean difference (SMD) with a confidence interval (CI) of 95%. A majority of the studies showed a low or moderate risk of bias. Meta-analysis showed significantly higher levels of vitamin B12 in postoperative patients administered with microecological preparations (SMD = 0.52; 95% CI = 0.08–0.95; P = 0.02 ). There were no significant differences in QoL (SMD = −0.14; 95% CI = −0.45–0.17; P = 0.38 ), EWL (SMD = 0.45; 95% CI = −0.16–1.05; P = 0.15 ), and levels of TNF- α (SMD = −0.29; 95% CI = −0.64–0.05; P = 0.09 ), interleukin 6 (SMD = −0.1; 95% CI = −0.81–0.61; P = 0.78 ]), and CRP (SMD = 0.02; 95% CI = −0.32–0.36; P = 0.93 ). The trials examined indicated that microecological preparations had limited efficacy in improving QoL, EWL, and inflammatory response, but they stimulated the synthesis of vitamin B12 . This may help in designing efficient microecological preparations to supplement bariatric surgery in obese individuals.